«Просвіти» й уявлення про «поживну» літературу для народу в українській публіцистиці Наддніпрянщини на початку ХХ ст. - Волошенко, Вікторія; Voloshenko, Viktoriia (My University, 2016)
У статті на основі публікацій в українських періодичних виданнях початку ХХ ст. зроблено спробу проаналізувати винесені на суспільне обговорення компоненти й варіації уявлень про «поживну» літературу для народу українських діячів, дотичних діяльності «Просвіт» Наддніпрянщини (1906–1916 рр.)The article is dedicated to the analysis of components and variations in visions of the «useful» popular literature by Ukrainian leaders being the members of «Prosvita» branches in Dnieper Ukraine (1906-1916) or views of those who wrote about the activities of the above organization. The basic information for the analysis is taken from the articles of the Ukrainian editions released at the beginning of the XXth century.
«Prosvita» and Vision of «Useful» Popular Literature in Ukrainian Publications of Naddnipryanshchina at the Beginning of the XXth Century
Keywords: «Просвіта»; Наддніпрянська Україна; «Prosvita»; Dnieper Ukraine; Ukrainian nation; leaders of Ukrainian national movement; popular literature